Variations in individual player area in youth football matches: the effects of changes of players’ age, numerical relations, and pitch zones - Coito, Nuno (2022)
The aim of the study was to quantify the individual player area (IPA)that emerges during football matches at youth levels, consideringdifferent numerical relations and pitch zones. Two hundred andtwenty-eight players, divided by U15, U17 and U19, participated inthe study. Jonckheete-Terpstra and Kruskal Wallis nonparametrictests were used to compare the IPA according to variations inplayers’ age, numerical relations and pitch zones considered foranalysis. All ages and numerical relation results revealed the highestIPA in the zones closer to the goal and were lower in the middle ofthe pitch. For 3 × 3 to 10 × 10 numerical relations, the IPA washigher in the U15 and lower in the U17. The greater differencesbetween the age groups concerned numerical relations of 6 × 6 to10 × 10 (p ≤ 0.001). The effect size was moderate between the U15and U17 in numerical relations of 8 × 8 to 10 × 10. Results suggestthat the manipulation of IPA during training sessions should respectplayers’ age and be adjusted considering the numerical relation andthe tactical purpose of coaches.